Extension Education: How do we learn best? - Soehner, Madalyn; Johnson, Wendy (My University, 2018)
Due to the rise of new educational methods, one may begin to wonder, what is the best way to learn information? Can these new methods truly replace traditional methods? This experiment evaluated the effectiveness of an infographic to a text based on amount of information retained and personal preference. This study also examines if professional status has an effect on information retention. In order to answer these questions, subjects were given a copy of an infographic and a journal article covering the same information. The subjects were then given 5 minutes to look over both materials and to answer four comprehensive questions. After completing this portion, the subjects were then asked to complete a survey analyzing the effectiveness of the methods and their personal preferences. The results yielded that an infographic is a better than a journal article for distributing information to both students and extension personnel.
Keywords: Fall 2018